2022
DOI: 10.1039/d2ra01578a
|View full text |Cite
|
Sign up to set email alerts
|

Beshanzuamide A, an unprecedented prenylated indole alkaloid produced by Aspergillus sp. Y-2 from the critically endangered conifer Abies beshanzuensis

Abstract: A structurally unprecedented prenylated indole alkaloid, together with five known analogues, was isolated from an endophytic fungus associated with the endangered conifer Abies beshanzuensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Y-2 obtained from Abies beshanzuensis , has an unprecedented prenylated indole alkaloid skeleton. 5 A biosynthetic pathway to beshanzuamide A 5 has been proposed. The structure of chevalinulin A 6 , a metabolite of the deep-sea cold-seep-derived fungus Aspergillus chevalieri CS-122, was established by X-ray analysis.…”
mentioning
confidence: 99%
“…Y-2 obtained from Abies beshanzuensis , has an unprecedented prenylated indole alkaloid skeleton. 5 A biosynthetic pathway to beshanzuamide A 5 has been proposed. The structure of chevalinulin A 6 , a metabolite of the deep-sea cold-seep-derived fungus Aspergillus chevalieri CS-122, was established by X-ray analysis.…”
mentioning
confidence: 99%
“…Y-2 harbored on needles of Abies beshanzuensis led to the identification of a new compound, beshanzuamide A (98), together with five known isolates: 72, 85, 89, 91, and asperochramide A (99). None of the metabolites displayed any obvious activity against A549 or HeLa cells with IC 50 values beyond 50 µM [45].…”
Section: Diketopiperazine Alkaloidsmentioning
confidence: 94%
“…The endophytic fungus A. fumigatus LN-4 separated from the stem bark of Melia azedarach generated 24 natural products containing 24, 26, tryprostatin A (29), brevianamide F (30), fumitremorgin B (31), verruculogen (32), cyclotryprostatin B (33), cyclotryprostatin A (34), verruculogen TR-2 (35), 12β-hydroxy-13α-methoxyverruculogen TR-2 (36), and 12βhydroxyverruculogen TR-2 (37), fumitremorgin C (38), terezine D (39), and cyclo-(Pro-Gly) (40), cyclo-(Pro-Ala) (41), cyclo(D-Pro-L-Ala) (42), cyclo-(Pro-Ser) (43), cyclo-(Ser-trans-4-OH-Pro) (44), cyclo-(Leu-4-OH-Pro) (45), cyclo-(Alatrans-4-OH-Pro) (46), cyclo-(cis−OH-D-Pro-L-Phe) (47), cyclo-(Gly-Phe) (48), cyclo-(Pro-trans-4-OH-Pro) (49), and cyclo-(Gly-Ala) (50) [31]. Continuing research on the fungus A. fumigatus LN-4 using the one strain many compounds (OSMAC) method, compound 25, 12α-fumitremorgin C (51), and 18oxotryprostatin A (52) were also identified [32].…”
Section: Diketopiperazine Alkaloidsmentioning
confidence: 99%
“…Li et al 112 characterised secondary metabolites from the fresh leaves of Pinus yunnanensis. Li et al 113 characterized beshanzuamide A, an indole alkaloid from the critically endangered conifer Abies beshanzuensis. Alam et al 114 reported on isolation, identification and DFT studies of two compounds from Bixa orellana.…”
Section: Nuclear Shielding Calculation In Natural Productsmentioning
confidence: 99%